Traumatic Luxation of the Eye Ball with Optic Nerve Transection Following Road Traffic Accident: Report of Two Cases and Brief Review of Literature - Roka, Narayani; Roka, Yam Bahadur (Nepalese Journal of Ophthalmology, 2018)
Background: Traumatic luxation of the eye ball is rare with only 106 cases reported in PubMed till date. The anatomic location of the eyeball within the socket and the resilience of the globe to pressure force, attachment to extraocular muscles and optic nerve prevents luxation during trauma. Case: Road traffic accidents (RTA) is the most common cause for these injuries and the outcome can vary from complete recovery on repositioning to visual loss due to globe perforation or optic nerve injury. We report two unique cases of traumatic right globe luxation and complete optic nerve transection due to RTA and give a brief review of literature. Conclusion: RTA leading to eye ball luxation though rare can be a challenging situation when encountered. Given the limited time for the salvage of the eye early intervention is not always possible especially in developing countries where there is delay in reaching the hospital. Despite all these confounding factors attempt must be made to salvage the eye either for functional, cosmetic or psychological reasons.